2015
DOI: 10.1111/ijac.12381
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Elastic Properties for a Wound Oxide Ceramic Matrix Composite Material

Abstract: This study presents enhanced studies of inverse approach of the classical laminate theory for prediction of the elastic properties of a wound oxide ceramic matrix composites material (CMC). Based on mechanical tests and microstructure analysis, elastic properties of virtual equivalent unidirectional layers were calculated. To adapt the analytical model to CMCs from different batches which show various fiber volume contents, porosities, and different fiber orientations, a scaling factor Ω was introduced with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This effect is dominant in the above-mentioned fiber orientations and results in a relatively weaker matrix with lower stiffness when compared with other fiber orientations. This phenomenon is discussed in detail in previous work [38].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…This effect is dominant in the above-mentioned fiber orientations and results in a relatively weaker matrix with lower stiffness when compared with other fiber orientations. This phenomenon is discussed in detail in previous work [38].…”
Section: Resultsmentioning
confidence: 62%
“…The in-plane elastic properties of the virtual UD layers for both the materials are listed in Table 3. The values of WHIPOX™ are taken from a previous publication [38]. In the case of C/C-SiC, the values of the UD values were evaluated from data fitting for other fiber orientations.…”
Section: Elastic Behaviormentioning
confidence: 99%
“…A number of problems impede this procedure: a transfer of the mechanical properties of unidirectional plies to the laminate is only valid for a limited extent, referring to the sintering behavior of the matrix which depends on the fiber orientations of the laminate. 7 In addition, the layer interface properties are unknown and the composite is ground before application, which blurs the information of the layer structure. Consequently, in this work the material is assumed to be homogeneous and orthotropic, so it is regarded from a macroscopic point of view ignoring the layered structure.…”
Section: Modeling the Anisotropic Deformation Behavior Of Whipox®mentioning
confidence: 99%
“…[3][4][5] For the material WHIPOX Õ this approach was pursued in a PhD thesis. 6 In another work 7 an inverse laminate theory is applied on experimental data of tensile tests of WHIPOX Õ in order to determine the elastic properties of single unidirectional laminae. These approaches could not be generalized because a number of practical problems impede the transfer of a microstructural analysis to a macro-scale model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that filament winding is a promising manufacturing technique, as compared to the use of textile preforms, to attain reinforcement in arbitrary directions within CMC structures [9,17]. A novel manufacturing method utilizing wet filament wind unidirectional carbon fiber perform and liquid silicon infiltration (LSI) has been develop by the German Aerospace Institute (DLR) to manufacture state-of-the-art C/C-SiC structures [18].…”
Section: Introductionmentioning
confidence: 99%